ARAH WARNA KAIN KATUN DENGAN PEWARNA ALAMI DARI BUAH PINANG (Areca catechu) DAN KAYU ULIN (Eusideroxylon zwageri) DENGAN BERBAGAI FIKSATO - Dwi Mulya Iswaningsih; Masriani; Firman Shantya Budi (Postgraduate, University of Mataram, 2026)
The textile industry in Indonesia contributes significantly to the country’s foreign exchange earnings, but synthetic dye waste has a negative impact on the environment. Natural dyes derived from plant waste can serve as an environmentally friendly alternative, but previous research has had limitations, such as low colorfastness, unstable colors, low pigment concentration, and suboptimal extraction and fixation methods. This study used 10 × 10 cm pieces of Hero cotton fabric dyed with natural dyes derived from areca nuts (*Areca catechu*) and ironwood (*Eusideroxylon zwageri*), which contain tannins that produce brown hues. The research process included scouring, mordanting, dyeing, fixation, and wet rub testing using 1% fixatives consisting of alum, lime, vinegar, tunjung salt, softener, and lemon. Color analysis was performed colorimetrically using a colorimeter app on an Android smartphone with L*, a*, and b* parameters. The results showed that all fixatives except lime increased brightness (L*). Alum, softener, and lemon reduced red intensity, while lime, vinegar, and rock salt increased it. All fixatives except lime reduced yellow intensity. The wet rub test caused an increase in brightness as well as a decrease in red and yellow intensity on the fixed fabric.